2000
DOI: 10.1016/s0012-9593(00)00109-9
|View full text |Cite
|
Sign up to set email alerts
|

Bilinear space-time estimates for homogeneous wave equations

Abstract: In this paper, we pursue a systematic treatment of the regularity theory for products and bilinear forms of solutions of the homogeneous wave equation. We discuss necessary and sufficient conditions for the validity of bilinear estimates, based on L2 norms in space and time, of derivatives of products of solutions. Also, we give necessary conditions and formulate some conjectures for similar estimates based on LqtLxr norms

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
156
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(161 citation statements)
references
References 20 publications
5
156
0
Order By: Relevance
“…We have the following estimate for products of solutions to these; see [10] for similar results with an additional average in time.…”
Section: The Wave Equation: Product Of Solutions Consider Solutions mentioning
confidence: 83%
“…We have the following estimate for products of solutions to these; see [10] for similar results with an additional average in time.…”
Section: The Wave Equation: Product Of Solutions Consider Solutions mentioning
confidence: 83%
“…2 As a simple example, take a generic system of equations of the form 2Ψ I = Ψ I ∇Ψ I . It can be shown that these will not be locally well posed for regularities at the level of H 1 or below (see [24]), even though they have the same scale transformations as (5)- (6). Furthermore, smooth solutions to these generic equations will blow up in finite time even for small initial data.…”
Section: φ(·) λφ(λ·) (6)mentioning
confidence: 99%
“…This is a huge blow to any usual type of iteration procedure, because dispersive type space-time estimates of the form 5 L q (L r ) play a central role in obtaining inductive estimates. 6 Nevertheless, it turns out that the dangerous part of the curvature F MKG which does not exhibit any extra space-time estimates miraculously cancels itself where it appears in the equation (7) for the scalar field φ! This allows one to recover enough space-time estimates for solutions to that equation so that one may prove local existence and uniqueness (again, in the appropriate sense) for the system (2) with initial data taken in the Sobolev spaces H s for any 1 2 < s. This provides the first example of an equation coming from (3 + 1)-dimensional gauge field theory where (part of) the local well-posedness conjecture contained in [13] can be verified.…”
Section: φ(·) λφ(λ·) (6)mentioning
confidence: 99%
See 2 more Smart Citations